Gender Differences in Early Outcomes of Minimally Invasive Cardiac Surgery: A Cross-Sectional Analysis - Muhammad Yasir Khan, Adnan Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Minimally invasive cardiac surgery via right mini-thoracotomy has become increasingly popular for mitral valve interventions and coronary artery bypass grafting owing to reduced surgical trauma and accelerated recovery. However, anatomical and physiological differences between men and women may influence intraoperative complexity and early postoperative outcomes. Objective: To compare early outcomes of minimally invasive cardiac surgery in male versus female patients at a tertiary referral centre. Methods: A descriptive cross-sectional analysis was performed on 160 consecutive adults (104 men, 56 women) who underwent elective minimally invasive mitral valve repair/replacement or single-/double-vessel coronary bypass on cardiopulmonary bypass at Mukhtar A. Sheikh Hospital, Multan, between February 1, 2022 and February 28, 2023. Primary endpoints were 30-day all-cause mortality and major adverse cardiac and cerebrovascular events (MACCE). Secondary endpoints included cardiopulmonary bypass (CPB) time, aortic cross-clamp time, intraoperative transfusion volume, new-onset atrial fibrillation, re-exploration for bleeding, and lengths of intensive care unit (ICU) and total hospital stay. Continuous variables were compared by Student’s t-test and categorical variables by chi-square or Fisher’s exact test, with p<0.05 denoting significance. Results: Women were older (61.5 ± 9.7 vs. 58.3 ± 10.4 years; p=0.02) and had lower body surface area (1.70 ± 0.20 vs. 1.91 ± 0.21 m²; p<0.001). Mean CPB time was longer in women (112 ± 20 vs. 105 ± 18 min; p=0.02), as was cross-clamp time (82 ± 15 vs. 77 ± 14 min; p=0.03) and operative duration (190 ± 35 vs. 180 ± 30 min; p=0.04). Thirty-day mortality (1.8% vs. 1.9%; p=0.95) and MACCE rates (8.9% vs. 7.7%; p=0.80) were equivalent. Rates of new atrial fibrillation (19.6% vs. 16.3%; p=0.59) and re-exploration for bleeding (3.6% vs. 1.9%; p=0.47) did not differ. ICU stay (2.2 ± 0.8 vs. 2.0 ± 0.7 days; p=0.16) and total hospital stay (6.5 ± 1.6 vs. 6.2 ± 1.4 days; p=0.22) were similar. Conclusion: Although women undergoing minimally invasive cardiac surgery experienced slightly longer operative times, early morbidity and mortality were equivalent to those of men. These findings support the safety and efficacy of right mini-thoracotomy approaches across genders. Keywords: Minimally invasive cardiac surgery; gender differences; early outcomes; cross-sectional study; mini-thoracotomy.